In-depth free fatty acids annotation of edible oil by mCPBA epoxidation and tandem mass spectrometry. (16th April 2022) - Wang, Xiao; Li, Yuze; Jiang, Yuming; Meng, Lingwei; Nie, Zongxiu
Highlights: Epoxidation reaction coupled with mass spectrometry for in-depth structural characterizing free fatty acids in edible oil. Low-abundant free fatty acids were detected directly in the presence of high-abundant components. New carbon-carbon double bond location isomers were found in edible oil. Abstract: The analysis of free fatty acids (FFAs) in edible oils, especially their fine structure, can provide information for nutritional value evaluation and authentication. Here, a strategy based on epoxidation reaction by mCPBA combined with tandem MS was developed to identify and relatively quantify FFAs, including CC location isomers, which can rapidly distinguish different edible oils. Notably, low-abundant FFAs can be detected directly in the presence of high-abundant triacylglycerol (TAG) without complicated pretreatment. We identified a series of CC location isomers via mCPBA-nanoESI-MS/MS, among them, FA 24:1 (Δ13) and FA 24:1 (Δ17) were first identified in edible oils, and the predominant UFAs was FA 18:1 (Δ9), which occupies 98.35% of FA 18:1 in peanut oil while 89.68% in rapeseed oil. The results demonstrated that the proposed method could provide further in-depth CC positional information of oils, promoting the development of structural determination of fatty acids in food chemistry.